(untitled) (Journal of Basic and Applied Research in Biomedicine, 2022)
Background: Despite the considerable research efforts that have been made by Reproductive Biologists to understand the etiologies of male infertility, idiopathic male factor infertility still remains unexplained. It occurs in about 10% cases of infertility. Since the etiologies cannot be identified using routine semen analysis, it is important to identify cellular and sub-cellular sperm complications that may help to explain the cause(s) of the infertility, thus stimulate caregivers to direct the further work-up, diagnosis and counseling of affected individuals. The objective of this study was to determine seminal plasma creatine kinase (CK) activity and malondialdehyde (MDA) concentration among normozoospermia but infertile males. Materials and Methods: After routine semen analysis, seminal plasma CK activity and MDA were determined among 75 normozoospermia but infertile men and 50 men of proven fertility using spectrophotometric method. Unpaired Students-t-test and regression analysis were used to compare and associate CK activity and MDA concentration with sperm characteristics. Results: Significantly higher (p<0.001) level of MDA and CK activity were observed among infertile subjects than control group. Sperm count, percent motility, and viability were significantly lower (p<0.05) among study participants than control subjects. Similarly, percentage abnormal morphology was significantly higher (p<0.05) among infertile subjects than control group. The Odds of elevated CK activity to impair sperm motility, viability and morphology were 9.12(CI 102.6, 318.3), 3.18 (CI 129.9, 170.8) and 1.9 (CI 192.2, 208.1) times respectively higher among infertile group than controls. Similarly, the Odds of higher levels of MDA to impair sperm cell motility, viability and morphology were 5.02(CI 2.14, 4.6), 2.26(CI 2.34, 3.64) and 2.9 (CI 2.12, 3.73) times respectively higher among infertile group than control subjects. Conclusions: The seminal plasma CK activity and MDA constitute good indicators of functional metabolic activity and fertility potentials of spermatozoa among subjects with unexplained infertility.